2015
DOI: 10.1158/1078-0432.ccr-14-1686
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Tumor Microenvironment–Based Prognostic Score in Primary Operable Colorectal Cancer

Abstract: Purpose: The tumor microenvironment is recognized as an important determinant of progression and outcome in colorectal cancer. The aim of the present study was to evaluate a novel tumor microenvironment-based prognostic score, based on histopathologic assessment of the tumor inflammatory cell infiltrate and tumor stroma, in patients with primary operable colorectal cancer.Experimental Design: Using routine pathologic sections, the tumor inflammatory cell infiltrate and stroma were assessed using Klintrup-M€ ak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 26 publications
8
95
3
1
Order By: Relevance
“…We also assessed the overall parameters of inflammatory cell infiltrate and TSP by GMS, which did not confirmed statistically significant differences in DFS. Our observations are contrary to the results of Park et al (4). These differences may be due to sample size, nationality of the selected population and the scope of the TNM staging of patients enrolled in the study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We also assessed the overall parameters of inflammatory cell infiltrate and TSP by GMS, which did not confirmed statistically significant differences in DFS. Our observations are contrary to the results of Park et al (4). These differences may be due to sample size, nationality of the selected population and the scope of the TNM staging of patients enrolled in the study.…”
Section: Discussioncontrasting
confidence: 99%
“…The prognosis of patients is performed by staging of primary tumor and the involvement of metastases in the lymph nodes and distant organs by standard classification of the Union for International Cancer Control/American Joint Committee on Cancer (UICC/AJCC) classification based upon the tumor-node-metastasis (TNM) (2). However, recent reports in the literature indicated that a considerable heterogeneity of the primary tumor of colon cancer requires a more detailed qualitative analysis, all of its components such as inflammatory response and connective tissue stroma (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Histopathological reporting confirmed stage I, stage II and stage III disease in 7%, 52% and 41% of patients respectively. Mismatch repair status has previously been reported in a subset of this cohort and was available for 205 patients; 17 30 patients (15%) had mismatch repair deficient colorectal cancer.…”
Section: Resultsmentioning
confidence: 95%
“…13 Indeed, combined assessment of KM grade and TSP, termed the Glasgow Microenvironment Score (GMS), stratified survival greater than either measure alone, and in particular further stratified survival of those patients with a weak local inflammatory cell infiltrate. 17 However, whether inclusion of a potentially more detailed measure of the inflammatory cell infiltrate, such as the Immunoscore, may alter the prognostic value of the tumor-associated stroma is not clear. Therefore, the present study of patients undergoing potentially curative resection of stage I-III colorectal cancer has two aims: to compare the prognostic value of assessment of the inflammatory cell infiltrate using the KM grade and the Immunoscore, and to examine the clinical utility of combined assessment of the inflammatory cell infiltrate and TSP.…”
Section: Introductionmentioning
confidence: 99%
“…It may be useful to evaluate the level of immune involvement in the tumour microenvironment, and evaluate the degree of immune cell dysregulation prior to devising a patient treatment plan. Indeed, evaluation of immunological parameters is presently in development as a prognostic aid, and shows superior predictive ability compared with traditional histopathological staging methods in colorectal cancer (164)(165)(166) . Galon et al show that evaluation of the type, density and location of immune cell infiltration into tumours can allow prediction of patient survival (165) .…”
Section: Immunometabolism In Obesity and Cancermentioning
confidence: 99%